Solar Cells: Homo‐Tandem Polymer Solar Cells with VOC >1.8 V for Efficient PV‐Driven Water Splitting (Adv. Mater. 17/2016). Issue 17 (May 2016) - Gao, Yangqin; Le Corre, Vincent M.; Gaïtis, Alexandre; Neophytou, Marios; Hamid, Mahmoud Abdul; Takanabe, Kazuhiro; Beaujuge, Pierre M.
Abstract : On page 3366, P. M. Beaujuge and co‐workers describe homo‐tandem solar cells constructed by stacking identical subcells solution‐processed from blends of the wide‐bandgap polymer donor PBDTTPD and the fullerene acceptor PCBM, which achieve power conversion efficiencies >8% and open‐circuit voltages >1.8 V. The homo‐tandem devices provide sufficient voltage to induce the dissociation of water in an electrochemical cell. The authors acknowledge Hyun Ho Hwang (Heno) for developing the artwork.